Understanding Approaches to the Dorsal Hump - Barrett, Dane M.; Casanueva, Fernando; Wang, Tom (Facial Plastic Surgery, 2017)
Dorsal hump reduction is a central component of western aesthetic rhinoplasty. Surgical success begins with knowledge of aesthetic ideals and accurate preoperative analysis. Knowledge of the patient's distortion from aesthetic ideals informs approach, technique, and instrument selection. Both endonasal and external approaches are suitable for dorsal hump reduction, though the latter affords more versatility when other surgical modifications are necessary. The main techniques consist of en bloc, Skoog, and component resection. Each has their distinct advantage, though a surgeon's comfort level with each should impact technique selection. Completion of the dorsal reduction often leaves a defect that must be reconstructed. Failure to anticipate the potential long-term sequelae and appropriately manage the dorsal defect can lead to a poor result and patient dissatisfaction.
Keywords: aesthetic rhinoplasty; surgical techniques; dorsal hump; nasal surgery; dorsal hump reduction